SIMULATION OF THE ALCOHOL-OIL MIXTURE IN A T-SHAPED MICROCHANNEL USING THE DISSIPATIVE PARTICLE DYNAMICS METHOD ON GPU DEVICES - Horta, A. A.; Ferreira, L. O. S.; Martinez, E. L.; Maciel Filho, R. (Revista de Engenharia Térmica, 2014)
Multiphase fluid motion in microchannnels involves complicated fluid dynamics and is fundamentally important to diverse practical engineering applications. Among several applications, the alcohol-oil mixture is particularly important due to its application for biodiesel production. In this work, the mixture of immiscible fluids alcohol-oil in a square T-shaped microchannel was investigated using the Dissipative Particle Dynamics (DPD) method available in the HOOMD simulator, which runs on a single graphic processing unit (GPU). The immiscible fluids were achieved by increasing the repulsive force between species. The fluid properties and hydrodynamic behavior were discussed in function of model parameters. The simulation results agree with data published in the literature showing that the DPD is appropriate for simulation of mass transport on complex geometries in microscale on a single GPU.